Pyroptosis‐Inducing Biomaterials Pave the Way for Transformative Antitumor Immunotherapy - Hao Yin; Tanzhou Chen; Xiaoqu Hu; Wenting Zhu; Yida Li; Wenjie Sun; Lei Li; Hongmei Zhang; Qinyang Wang (Advanced Science)
Abstract Pyroptosis can effectively overcome immunosuppression and reactivate antitumor immunity. However, pyroptosis initiation is challenging. First, the underlying biological mechanisms of pyroptosis are complex, and a variety of gasdermin family proteins can be targeted to induce pyroptosis. Second, other intracellular death pathways may also interfere with pyroptosis. The rationally designed gasdermin protein‐targeting biomaterials are capable of inducing pyroptosis and have the capacity to stimulate antitumor immune function in a safe and effective manner. This review provides a comprehensive overview of the design, function, and antitumor efficacy of pyroptosis‐inducing materials and the associated challenges, with a particular focus on the design options for pyroptosis‐inducing biomaterials based on the activation of different gasdermin proteins. This review offers a valuable foundation for the further development of pyroptosis‐inducing biomaterials for clinical applications.